Neurosyphilis: A Comprehensive Review of Clinical Manifestations, Diagnosis, and Treatment - Pasha S A Rahil; Parimala S; Natarajan Arvind (Journal of Clinical and Biomedical Sciences)
Neurosyphilis, a sexually transmitted infection caused by Treponema pallidum, occurs when this organism breaches the central nervous system, particularly in individuals with compromised immune systems such as those living with HIV. Neurosyphilis remains a global health concern, and its prevalence has risen significantly, particularly among men who have sex with men (MSM) and among immunocompromised people, highlighting the importance of screening and public health interventions. Although neuroinvasion may happen at an early stage, the clinical signs might not appear until years later. Clinical presentations can differ from asymptomatic cases to serious complications such as meningitis and cognitive deficits. Diagnosis mainly relies on serological and cerebrospinal fluid (CSF) analysis. Penicillin remains the drug of choice, but alternative therapies may be necessary for penicillin allergy. Early detection and treatment significantly improve prognosis; however, late-stage cases may lead to permanent neurological damage. Increasing public awareness, providing education, and advancing research on diagnostic and treatment methods are essential to address the challenges of this re-emerging disease.